Using Solution focused practice with adults in health and social care - Milner, Judith, 1941-; Myers, Steve (John Stephen), 1959- (Jessica Kingsley Publishers, 2017)
An essential introduction which shows you how to work in solution focused ways with people in all stages of adulthood, including those with illness, mental disability and emotional trauma. It includes example activities that can be used to guide service users to use their own strengths to realize their personal goals.